Аналiз та інтеграція даних в сучасних розподілених web-системах - Стьопін, В. І.; Горбатенко, Б. В. (ХНУРЕ, 2019)
A method of data processing and integration is proposed. Nowadays, the majority of systems are distributed in some way and have both structured and raw data. Since cloud computing and storages become more and more popular, we have become to the task of data integration. In business, large databases can be created from databases of many other smaller companies. In a result, it turns out the system with real time updates and valid information. To achieve it, data should be transferred through secure and fast channels and be encrypted in an open-standard format such as XML or JSON. In Web surrounding many other factors are included and described in this article